Pendampingan Program Taman Pendidikan Al Qur’an (TPQ) di Desa Binor Kecamatan Paiton Probolinggo - Millah, Hayatul; Aziz, Abd. (KHIDMAH : Jurnal Pengabdian Masyarakat, 2021)
Abstract The aim of this community service activity is to provide an Islamic-based education platform, especially Qur'anic education for local residents and provide education to the general public so that they can obtain proper religious education. Programe implementation planning is compiled based on an analysis of environmental needs, determining objectives, developing curriculum, learning methods and the completeness of adequate facilities and infrastructure to carry out an educational program. Implementation of the Al-Qur’an Reading and Writing Learning Program using the Iqra' and Qiroati methods. The result of this service showed that the people of Binor Village, Paiton District, Probolinggo Regency can already read the Qur'an properly and correctly. Keywords : Qur'anic Education, Iqro'; Qiroati.